STUDENT’S ACTION WHEN FACED THE DIFFICULTY TO DO THE PROGRAMMING TASK DURING PANDEMIC COVID-19: SURVEY AT UNIVERSITI TEKNOLOGI MARA (UiTM) PAHANG - Mohd Rizal Bin Razak; Nor Zalina Binti Ismail; Ana Salwa Binti Shafie (Journal of Islamic, Social, Economics and Development, 2023)
The COVID-19 virus hit Malaysia starting in January 2020, and the Government of Malaysia enforced a Movement Control Order (MCO) beginning on March 18, 2020, to break the chain of COVID-19. During MCO, all the learning processes were conducted in Online Distance Learning (ODL) mode, including programming subjects taught at UiTM Pahang. This paper aims to know whether the students have difficulty completing a programming task during ODL and what actions they take to complete it. This research used the online survey using Google form as a medium to collect the data. The respondents of this research were 303 students from the Diploma of Computer Science and Diploma of Civil Engineering who took the introductory programming subject in September 2021. The data were analysed using SPSS statistical software. The findings of the research show that the majority of the students have difficulty completing the programming task. The students' preferred actions to complete the programming task are referring to their friends, searching for clues on the internet and referring to their lecturer. Based on the research findings, it is recommended that the instructor and faculty have a strong buddy-to-buddy (friend or senior) support system and a mentoring system to assist the students in programming tasks. This support system is essential because the students will succeed in programming if they can do a programming task well.